Inhibiting protein-protein interactions 2 - Whitty, Adrian (Henry Stewart Talks, 2014)
A different view of druggability, Five propositions about the druggability of PPI targets, Protein-ligand binding energy, Ligand efficiency and drug-target binding, ADME & druglikeness considerations, Conventional view of druglikeness, Druggability and chemical space, Targeting low druggability PPI, Macrocycles, Covalent inhibitors, Foldamers